Sunflower germin-like protein HaGLP1 promotes ROS accumulation and enhances protection against fungal pathogens in transgenic Arabidopsis thaliana - Beracochea, Valeria Cecilia (2015)
Germin-like proteins (GLPs) are a large, diverse and ubiquitous family of plant glycoproteins belonging to the Cupin super family. These proteins have been widely studied because of their diverse roles in important plant processes, including defence. The novel sunflower gene HaGLP1 encodes the first germin-like protein characterized from the family Asteraceae. To analyse whether constitutive in vivo expression of the HaGLP1 gene may lead to disease tolerance, we developed transgenic Arabidopsis plants that were molecularly characterized and biologically assessed after inoculation with Sclerotinia sclerotiorum or Rhizoctonia solani. HaGLP1 expression in Arabidopsis plants conferred tolerance to S. sclerotiorum at the first stages of disease and interfered with R. solani infection, thus giving rise to significant protection against the latter. Furthermore, HaGLP1 expression in Arabidopsis plants elevated endogenous ROS levels. HaGLP1-induced tolerance does not appear to be related to a constitutive induction of the plant defence or the ROS-related genes examined here. In conclusion, our data suggest that HaGLP1 is an interesting candidate for the engineering of plants with increased fungal tolerance and that this gene could also be useful for the selection of naturally overexpressing sunflower genotypes for conventional breeding purposes.